Agama Sebagai Kebutuhan Manusia Modern - Amalia, Ilma (Jurnal Garasi Buku dan Obrolan Keilmuan, 2024)
The Questions about religion always surround and occupy our minds. Nowadays, various problems arise that give birth to new ideologies in almost every religion. As time goes by, people are rethinking the need and function of religion in their lives. The purpose of writing this article is to explain religion as a basic need for every human being, including humans in this modern era. This article also discusses the definition of religion, the factors that encourage people to learn about religion, as well as the function and existence of religion in the modern era. The research method that the author uses in this article is a qualitative method with data sourced from library data. The findings obtained by the author through the research outlined in this article are that there are psychological factors that encourage humans to seek religion even though in their daily lives modern humans may avoid religious practices.